2011
DOI: 10.1116/1.3660784
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of graphene piezoresistors for use as strain gauge sensors

Abstract: The primary objective of this research is to fabricate a graphene-based piezoresistive strain gauge and characterize its sensitivity. The strain gauge consists of mechanically exfoliated graphene sheets and electrical electrodes located on a silicon wafer. Instead of using e-beam lithography, which is the most widely applied methods in experimental studies of graphene, a new fabrication method utilizing conventional photolithography was used to easily fabricate a new nanoelectromechanical system strain gauge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Lee et al reported that the gauge factor of graphene grown on Ni and Cu films by chemical vapor deposition was 6.1, with 1% applied strain [3]. Chen et al found that the gauge factor of mechanically exfoliated graphene was nearly 150 [4]. Hosseinzadegan et al reported that the gauge factor of graphene prepared by chemical vapor deposition on Si/SiO 2 wafer was 18,000 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that the gauge factor of graphene grown on Ni and Cu films by chemical vapor deposition was 6.1, with 1% applied strain [3]. Chen et al found that the gauge factor of mechanically exfoliated graphene was nearly 150 [4]. Hosseinzadegan et al reported that the gauge factor of graphene prepared by chemical vapor deposition on Si/SiO 2 wafer was 18,000 [5].…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles 1 , nanotubes 2 , nanowires 3 4 5 , thin films 6 7 8 ) and their assemblages have been attracting interest recently due to their strain sensing characteristics. For example, strain sensors comprised of carbon nanotubes (CNTs) 6 7 8 9 10 11 12 13 14 , zinc oxide nanowires 4 5 , or graphene 15 16 17 18 19 20 21 serve as good alternatives for developing new sensors because of their outstanding properties. For graphene-based sensors, the principal vibrational frequencies 15 and electrical conductance 16 of graphene strongly depend on its topological structure which can be modulated by applying uniaxial strain, making it useful for high sensitivity tensile strain sensing.…”
mentioning
confidence: 99%
“…Strain sensing is possible in graphene through several different methods. These include embedding GO in a stretchable polymer matrix, as seen in Reference [295] by Li et al and also in Reference [292] by Qin et al Further discussion on the stretchability of the C-C bonds in the embedded graphene can be found in the work of Chen et al [302]. Other methods involve the use of nanographene films with discrete islands in the film.…”
Section: Overview Of Previously Used Rfid Sensor Materialsmentioning
confidence: 99%
“…Other sensors have been outlined that use rGO for the sensing of gasses, such as NO 2 , NH 3 and CO, such as those found in the works of Le et al [287] and that of Lu et al [305]. It should be noted at this point that GO is itself hydrophilic [302] due to the presence of hydrophilic functional groups on its surface [287] and regular graphene exhibits quantum capacitive effects when exposed to humid environments [287,299]. Furthermore, the complete reduction of GO in some cases can be very difficult to achieve [297] and the use of this partial rGO is quite suitable for humidity sensing [304].…”
Section: Overview Of Previously Used Rfid Sensor Materialsmentioning
confidence: 99%